Triglyceride Level Is an Independent Risk Factor in First-Attacked Neuromyelitis Optica Spectrum Disorders Patients - Wu, Kaimin; Wen, LuLu; Duan, Ranran; Li, Yanfei; Yao, Yaobing; Jing, Lijun; Jia, Yanjie; Teng, Junfang; He, Qianyi (Frontiers in Neurology, 2019)
Abstract Objective To investigate prospective associations between triglyceride (TG) level and prognosis of first-attacked patients with neuromyelitis optica spectrum disorders (NMOSD). Methods This retrospective study included 196 patients newly diagnosed with NMOSD from June 2014 to December 2018. Data of clinical parameters, including age of onset, sex, BMI, blood lipid levels, anti-aquaporin-4 status, serum glucose level, therapy regimens, comorbidities, initial Expanded Disability Status Scale (EDSS), relapses, and outcomes were collected. We used logistic regression models to examine the associations among relevant clinical factors and outcomes, and statistical analyses were performed using the SPSS 23.0 software. Results Compared with the high TG group, residual EDSS was relatively lower in the normal TG group (median 1.0 vs. 2.0, P=0.002). In the univariate analysis, TG level was positively correlated with outcomes (OR 1.75, 95% CI 1.18-2.60, P=0.005) and relapses (OR 1.57, 95% CI 1.07-2.31, P=0.02). Our stratified analysis suggested that patients with normal BMI (OR 4.90,95% CI 2.10-11.44, P=0.001) were closely correlated with poor recovery owing to increased TG level. In the multivariate analysis, a statistically significant association still existed between TG level and outcomes (OR 3.44, 95% CI 1.02-11.64; P=0.040) after adjusting for various variables. Conclusions In first-attacked NMOSD patients, TG level was positively associated with poor recovery. Early monitoring and treatment of elevated TG level in NMOSD patients are important.